The scorch trials ebook - Dashner, James (Maze Runner, 2010)
The second book in the blockbuster phenomenon The Maze Runner series now features chapters from The Fever Code, the highly-anticipated conclusion to the MAZE RUNNER SERIES—the novel that finally reveals how the maze was built!       Thomas was sure that escape from the Maze would mean freedom for him and the Gladers. But WICKED isn’t done yet. Phase Two has just begun.    The Gladers have two weeks to cross through the Scorch—the most burned-out section of the world. And WICKED has made sure to adjust the variables and stack the odds against them.    Friendships will be tested. Loyalties will be broken. All bets are off.    There are others now. Their survival depends on the Gladers’ destruction—and they’re determined to survive.       The Maze Runner and Maze Runner: The Scorch Trials are now major motion pictures featuring the star of MTV's  Teen Wolf , Dylan O’Brien; Kaya Scodelario; Aml Ameen; Will Poulter; and Thomas Brodie-Sangster. The third movie, Maze Runner: The Death Cure , will hit screens in 2018.      Also look for James Dashner’s edge-of-your-seat MORTALITY DOCTRINE series!   Praise for the Maze Runner series: A #1 New York Times Bestselling Series A USA Today Bestseller A Kirkus Reviews Best Teen Book of the Year An ALA-YASLA Best Fiction for Young Adults Book An ALA-YALSA Quick Pick   "[A] mysterious survival saga that passionate fans describe as a fusion of Lord of the Flies , The Hunger Games , and Lost . "— EW   “Wonderful action writing —fast-paced …but smart and well observed.” — Newsday   “[A] nail-biting must-read.” — Seventeen   “Breathless, cinematic action. ”— Publishers Weekly   “ Heart pounding to the very last moment.”— Kirkus Reviews   “ Exclamation-worthy. ”— Romantic Times   “James Dashner’s illuminating prequel [ The Kill Order ] will thrill fans of this Maze Runner [series] and prove just as exciting for readers new to the series.”— Shelf Awareness , Starred " Take a deep breath before you start any James Dashner book."- Deseret News